Effect of dietary supplementation with Morinda citrifolia on productivity and egg quality of laying hens - Más-Toro, Dairon; Martínez-Aguilar, Yordan; Rodríguez-Bertot, Román; Betancur-Hurtado, Cesar; Rosabal-Nava, Osmani (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In order to evaluate the dietary supplementation of powdered leaves of Morinda citrifolia on productivity and egg quality of laying hens, a total of 160 White Leghorn birds (Hybrid L-33) of 27 weeks of age were allotted during 70 days, according to completely randomized design. Dietary treatments consisted of a control diet fed without or with 0.5, 1.0 and 1.5% of powdered leaves of M. citrifolia. Supplementation of 1.0 and 1.5% of M. citrifolia powder increased the egg weight (P&lt,0.05), however, laying intensity, body weight, feed intake, unsuitable eggs, eggshell surface, mass conversion, haugh units and height of the dense white and of the yolk showed no significant differences (P&gt,0.05) among treatments. Also, supplementation of 0.5 and 1.0% of M. citrifolia increased the shell thickness and the yolk color was pigmented by this medicinal plant. It recommended the dietary supplementation of 1.0% of powdered leaves of M. citrifolia on laying hen diets to improve the egg weight, shell thickness and yolk color.